NEGARA BERDASARKAN HUKUM (RECHTSSTAATS) BUKAN KEKUASAAN (MACHTSSTAAT) - Zahermann Armandz Muabezi (Puslitbang Hukum dan Peradilan Mahkamah Agung RI, 2017)
The vision of the rule of law was first forwarded by Plato and then confirmed by Aristotle. Plato’s concept stated that a good state administration is based on a good (law) arrangement, this term called nomoi. In further development Rudolf von Gneist name this term with rechtsstaat where earlier Albert Venn Dicey named it the rule of law. In principle rechtsstaat or rule of law aims to limit the rulers (government in a broad sense) attitudes and acts based on laws and regulations that apply at a certain place and time on the people. The doctrine of rechtsstaats or rule of law can only grow in a democratic country. Without the rule of law and democracy there will be only totalitarian, fascist, absolute and repressive ideology. Politics becomes the highest commander where the law become a means of maintaining the power which is inconsistent with the government. This form is called the state of power (machtsstaat). This article is trying to use empirical analysis. The doctrine of the state of law and democracy are both the attributes of the modern state of a political system built more than two centuries ago. The transformation of the democratic transition ensures that authoritarian rule becomes democracy based on the rule of law implying that both can be achieved together by involving all stakeholders given their respective roles and chance simultaneously according to the agreement.Keywords : rule of law, power sate, rule of law measurement, democracy